Gob’s Circles of a Triangle in the Isotropic Plane - Ružica Kolar-Šuper (Journal of Mathematics)
In this paper, we consider Gob’s circles of an allowable triangle in the isotropic plane and derive their equations in the case of a standard triangle. We prove that the potential axes of the circumscribed circle and Gob’s circles are the angle bisectors of the given triangle. We investigate some other interesting properties of Gob’s circles and some other circles related to the given triangle.